2002
DOI: 10.1262/jrd.48.497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose of hCG on Induction of Fertile Estrus in Shiba Goats Pretreated Intravaginally with Progesterone during the Early Postpartum Nursing Period.

Abstract: Abstract. The present study was conducted to determine the effect of a low dose of human chorionic gonadotropin (hCG) on the induction of fertile estrus in Shiba goats pretreated intravaginally with progesterone during the early postpartum period. Nursing Shiba goats (n=13) around 3 weeks after the parturition were pretreated with a controlled internal drug release dispenser (CIDR) containing 0.3 g of progesterone for 7 day, and 60 µg of cloprostenol 24 hr before CIDR removal. Goats in Group I (n=6) received s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…The concentration of estradiol-17β in blood plasma was measured by RIA as described previously [13][14][15][16]20]. The concentration of progesterone in blood plasma was measured by RIA using the processed standard curve as described previously [13][14][15][16]20].…”
Section: Hormone Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of estradiol-17β in blood plasma was measured by RIA as described previously [13][14][15][16]20]. The concentration of progesterone in blood plasma was measured by RIA using the processed standard curve as described previously [13][14][15][16]20].…”
Section: Hormone Assaysmentioning
confidence: 99%
“…The concentration of progesterone in blood plasma was measured by RIA using the processed standard curve as described previously [13][14][15][16]20]. Anti-estradiol-17β-6-BSA serum (GDN no.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…It has also been shown that suckling delays postpartum ovarian resumption in Japanese Black cows [25]. Another explanation for why more culture-competent oocytes were collected in the weaned group might be that normal growth of follicles and oocytes requires normal gonadotropin secretion and that gonadotropin secretion is inhibited in early postpartum suckled beef cows [26][27][28][29]. Since normal follicular and oocyte growth is probably necessary for normal development of blastocysts in vitro, the effects of suckling on the plasma FSH and LH profiles and follicular profiles (number and size) around the time of OPU in Japanese Black cows should be clarified in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of progesterone in blood plasma was measured by RIA as described previously, [12,19] using the processed standard curve. Anti-progesterone-11-BSA serum (GDN no.…”
Section: Hormone Assaysmentioning
confidence: 99%
“…The concentration of estradiol-17β in the plasma was measured by RIA, as described previously [12,19]. Before the samples were assayed, the accuracy of the assay was estimated using the processed standard curve.…”
Section: Hormone Assaysmentioning
confidence: 99%